2016
DOI: 10.1002/atr.1393
|View full text |Cite
|
Sign up to set email alerts
|

Public transit service operation strategy under indifference thresholds‐based bi‐modal equilibrium

Abstract: Summary This paper investigates public transit service (fare and frequency) operation strategies in a bi‐modal network with assumption of indifference thresholds‐based travelers' mode choice behavior. Under such behavior, users would switch to a new mode only if its utility is larger than the utility of current mode plus a threshold. The concept of indifference thresholds‐based bi‐modal equilibrium (ITBE) and the properties of the ITBE solution are explicitly proposed. Considering transit operator's different … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 35 publications
0
3
0
1
Order By: Relevance
“…Different fare structures are mainly used as one of the indicators for evaluating passenger travel behavior, operator performance, and other aspects. For flat fare structure (FF) optimization, Wang et al [14] investigated public transit service (i.e., flat fare and frequency) operation strategies in a bimodal network. Jin et al [11] focused on a flat fare structure and found that low fares are preferable from the viewpoint of maximizing social welfare.…”
Section: Introductionmentioning
confidence: 99%
“…Different fare structures are mainly used as one of the indicators for evaluating passenger travel behavior, operator performance, and other aspects. For flat fare structure (FF) optimization, Wang et al [14] investigated public transit service (i.e., flat fare and frequency) operation strategies in a bimodal network. Jin et al [11] focused on a flat fare structure and found that low fares are preferable from the viewpoint of maximizing social welfare.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, a practical MSDEDM example of highway emergency is given to illustrate the effectiveness and practicability of the proposed dynamic fuzzy approach. Remarkably, the application implies that the fuzzy theory can well handle the uncertainty of real world in practice and have wide application prospect in other related fields, such as public transport [36][37][38], logistics network [39][40][41], and traffic management [42]. e method of the dynamic decision-making procedure would be a useful reference to the similar decision-making researches.…”
Section: Discussionmentioning
confidence: 99%
“…Cantillo et al [20] designed a state choice survey that the subjects are faced with two alternatives, but they are allowed to choose an indifferent potion, such as ''both are the same'' and established a discrete choice model to inspect the individuals' choice behaviors with indifference threshold. Wei et al [21] and Wang et al [22] proposed the notion of indifference thresholds-based bi-modal equilibrium (ITBE) with the assumption of indifference thresholdsbased travelers' mode choice behavior. They indicated that the solution of ITBE might not be unique by assuming travelers have different indifferent threshold for different modes.…”
Section: Introductionmentioning
confidence: 99%